2002
DOI: 10.1161/01.cir.0000021426.87274.62
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CYR61, an Angiogenic Immediate Early Gene, in Arteriosclerosis and Its Regulation by Angiotensin II

Abstract: Background-The renin-angiotensin system is thought to be involved in development and progression of arteriosclerosis, thereby contributing to adverse cardiovascular events. To elucidate the role of angiotensin II (Ang II) at a cellular level, we analyzed the Ang II-induced gene expression profile. Methods and Results-Genes induced on Ang II stimulation (10 Ϫ7 mol/L, 45 minutes) in rat smooth muscle cells were analyzed by polymerase chain reaction selected subtraction. In addition to known genes, such as interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 39 publications
5
90
0
3
Order By: Relevance
“…Previous reports showed that Cyr61 is expressed in endothelial and smooth muscle cells in the developing mouse blood vessels (34,35) but only weakly in vessels of normal adult mice and humans (36). In the present study, Cyr61 was expressed in normal afferent and efferent arterioles, in which Cyr61 expression might be upregulated by strong mechanical stretch due to shear stress (37).…”
Section: Discussionsupporting
confidence: 59%
“…Previous reports showed that Cyr61 is expressed in endothelial and smooth muscle cells in the developing mouse blood vessels (34,35) but only weakly in vessels of normal adult mice and humans (36). In the present study, Cyr61 was expressed in normal afferent and efferent arterioles, in which Cyr61 expression might be upregulated by strong mechanical stretch due to shear stress (37).…”
Section: Discussionsupporting
confidence: 59%
“…In addition, it has been shown that angiotensin II infusion into hyperlipidemic mice augments lesion formation independently of elevations in blood pressure by eliciting a Th1 response 25 or by increasing the angiogenic properties of the plaque. 26 Despite the multipotent ability of angiotensin II to affect plaque vulnerability, our data show that intraplaque hemorrhages occurred in the lowered shear stress lesions only in response to angiotensin II stimulation.…”
Section: Cheng Et Al Shear Stress and Atherosclerosis 2749mentioning
confidence: 56%
“…These included: (1) the ECM proteins fibronectin, vitronectin, and fibrinogen, and (2) the proteins Cyr61 and plasminogen, which are overexpressed or become ECM-associated during the inflammatory responses. 22,23 Furthermore, cell adhesion to VCAM-1 was tested because it represents an established ␣ D ␤ 2 ligand. 1 Additionally, cell adhesion to the fibrinogen P2-C peptide, which duplicates the binding site for ␣ M ␤ 2 in fibrinogen 24 and contains the generic recognition information required for ␣ M ␤ 2 binding, 25 was examined.…”
Section: Analyses Of Ligand-binding Properties Of Integrinmentioning
confidence: 99%